INFLUENCE OF SELECTED PARAMETERS OF MATING VOCALIZATION OF PHEASANTS (PHASIANUS COLCHICUS) ON REPRODUCTIVE SUCCESS - Piotr Czyżowski; Sławomir Beeger (Polish Journal of Natural Sciences, 2024)
The purpose of this study was to analyze the mating vocalizations of pheasant roosters (time between successive vocalizations, peak frequency of sound amplitudes) and to demonstrate the relationship between vocalization parameters and the number of hens accumulated by the roosters (reproductive success). The research was conducted based on recordings of the sounds of 6 rolling roosters. A total of 79 isolated vocalizations constituted the study material. The recordings were made using a Zoom H1 portable sound recording device based on two microphones in an X/Y arrangement, enabling correct recording of stereophony. Roosters leading two or one hen were characterized by more active vocalizations, which increases their attractiveness to hens choosing them. Cooks leading two or one hen were characterized by a lower peak frequency of the vocalization sound produced than roosters without hens. This may indicate that roosters making sounds at lower frequencies are more attractive to hens.